ARNAWLÍ MEKTEPLERDE KVARKLARDIŃ QÁSIYETLERIN OQÍTÍW METODIKASÍ - Jumamuratov, A.; Bayımbetova, A. (SCIENCE and SOCIETY, 2025)
The article provides methods for teaching the properties of quarks in physics lessons in specialized schools through the application of innovative technologies and demonstrates an increased level of knowledge acquisition.